Tracing fairness intentions: Chinese whisper - Zulia Gubaydullina; Kilian Bizer (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2008)
The paper aims at defining the role of intentions for reciprocity. The ultimatum game is modified, by adding a kind of randomizer (Chinese Whisper), to generate outcomes which are not intended und thus to separate the proposers' initial intentions from their actual offers. The mechanism ensures that the responder reacts to changing intentions and not to changing outcomes. This experimental approach also has the advantage that the number of available options for the proposer is not limited. Our evidence supports the view that fairness theory should explicitly address intentions responders exhibit different acceptance rates depending on the intentions of proposers.
Keywords: C72; C91; 330; Fairness; Reciprocity; Intention; Ultimatum game